2002
DOI: 10.1038/417405a
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin 2 transmits the behavioural circadian rhythm of the suprachiasmatic nucleus

Abstract: The suprachiasmatic nucleus (SCN) controls the circadian rhythm of physiological and behavioural processes in mammals. Here we show that prokineticin 2 (PK2), a cysteine-rich secreted protein, functions as an output molecule from the SCN circadian clock. PK2 messenger RNA is rhythmically expressed in the SCN, and the phase of PK2 rhythm is responsive to light entrainment. Molecular and genetic studies have revealed that PK2 is a gene that is controlled by a circadian clock (clock-controlled). Receptor for PK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
589
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 652 publications
(617 citation statements)
references
References 48 publications
25
589
1
2
Order By: Relevance
“…These receptors, named prokineticin receptor 1 and 2 (PKR-1 and PKR-2), belong to the family of G-protein-coupled receptors, share approximately 85% amino-acid identity and are about 80% identical to the previously described mouse orphan receptor gpr73 (Parker et al, 2000). In mouse brain, PKR-2 mRNA is expressed in the lateral septal (LS) nucleus, paraventricular, parataenial and paracentral thalamic nuclei (PVT/PT/PC), paraventricular, dorsal medial and arcuate hypothalamic nuclei (PVH/DMH/ARC), suprachiasmatic nucleus (SCN), subfornical organ (SFO), lateral globus pallidus and amygdala (Cheng et al, 2002). In previous studies, we showed that these receptors are also expressed in rat spinal cord and dorsal root ganglia, bind Bv8 with high affinity, and, when activated by Bv8, produce [Ca þ 2 ] i transients in cultured dorsal root ganglion neurones (Negri et al, 2002).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…These receptors, named prokineticin receptor 1 and 2 (PKR-1 and PKR-2), belong to the family of G-protein-coupled receptors, share approximately 85% amino-acid identity and are about 80% identical to the previously described mouse orphan receptor gpr73 (Parker et al, 2000). In mouse brain, PKR-2 mRNA is expressed in the lateral septal (LS) nucleus, paraventricular, parataenial and paracentral thalamic nuclei (PVT/PT/PC), paraventricular, dorsal medial and arcuate hypothalamic nuclei (PVH/DMH/ARC), suprachiasmatic nucleus (SCN), subfornical organ (SFO), lateral globus pallidus and amygdala (Cheng et al, 2002). In previous studies, we showed that these receptors are also expressed in rat spinal cord and dorsal root ganglia, bind Bv8 with high affinity, and, when activated by Bv8, produce [Ca þ 2 ] i transients in cultured dorsal root ganglion neurones (Negri et al, 2002).…”
Section: Introductionmentioning
confidence: 89%
“…Common structural motives in this peptide family are the amino-terminal sequence of 20 amino-acid residues and the five disulphide bonds that link the 10 cysteine residues and fold the molecules into a globular form. The distribution of mRNAs of murine Bv8-like proteins has been reported in the brain, spinal cord, gastrointestinal tract, endocrine glands and other peripheral organs of mice and rats LeCouter et al, 2001;Li et al, 2001;Melchiorri et al, 2001;Cheng et al, 2002;Masuda et al, 2002). In the brain, the main localizations of mPK-2 include the olfactory bulb, cerebral cortex (in some neurones of layer II), dorsal and ventral hippocampus, medial preoptic area of the hypothalamus, suprachiasmatic nucleus (SCN), some thalamic nuclei, Purkinje cells of cerebellum, sensory and motor nuclei of the brain stem and spinal cord.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One candidate diffusible signal is prokineticin-2 (PK2) (Cheng et al, 2002). This protein is expressed rhythmically in the SCN, and its receptor is present in all major SCN targets (Cheng et al, 2002(Cheng et al, , 2005.…”
Section: Circadian Output and Orchestration Of Endocrine Function Difmentioning
confidence: 99%
“…This protein is expressed rhythmically in the SCN, and its receptor is present in all major SCN targets (Cheng et al, 2002(Cheng et al, , 2005. Likewise, PK2 administration during the night (when levels are low) inhibits wheel running behavior.…”
Section: Circadian Output and Orchestration Of Endocrine Function Difmentioning
confidence: 99%